1976
DOI: 10.4039/ent1081395-12
|View full text |Cite
|
Sign up to set email alerts
|

THE DISPERSAL OF LOPHYROPLECTUS LUTEATOR (HYMENOPTERA: ICHNEUMONIDAE) ON NEODIPRION SERTIFER (HYMENOPTERA: DIPRIONIDAE) IN SOUTHERN ONTARIO

Abstract: The introduced parasite Lophyroplectus luteator Thunberg has spread 305 km in an easterly direction in the 13 years since its release and has dispersed faster in southern Ontario than its host, Neodiprion sertifer (Geoffroy). The prevailing westerly winds were probably an important factor. The limited dispersal from a second liberation is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…The weak genetic structure we found for both parasitoid species matches the weak genetic structure recently described for the spruce budworm during the rising phase of the outbreak (Larroque et al, 2019). These results suggest that A. disperse 50-140 km per year from their release point (Quednau, 1990;Rose, 1976;West et al, 1994), which is comparable to observed dispersal distances of the spruce budworm (Boulanger et al, 2017;Greenbank et al, 1980) and the distances between subsets of the sampled outbreak areas in our study (Figure 2a). Thus, in continuous forested landscapes, insect parasitoids may contribute in many cases to spatial synchrony in outbreak patterns by means of the birdfeeder effect (Eveleigh et al, 2007;McCann & Rooney, 2009).…”
Section: Genetic Evidence Of Large-scale Population Connectivitysupporting
confidence: 90%
“…The weak genetic structure we found for both parasitoid species matches the weak genetic structure recently described for the spruce budworm during the rising phase of the outbreak (Larroque et al, 2019). These results suggest that A. disperse 50-140 km per year from their release point (Quednau, 1990;Rose, 1976;West et al, 1994), which is comparable to observed dispersal distances of the spruce budworm (Boulanger et al, 2017;Greenbank et al, 1980) and the distances between subsets of the sampled outbreak areas in our study (Figure 2a). Thus, in continuous forested landscapes, insect parasitoids may contribute in many cases to spatial synchrony in outbreak patterns by means of the birdfeeder effect (Eveleigh et al, 2007;McCann & Rooney, 2009).…”
Section: Genetic Evidence Of Large-scale Population Connectivitysupporting
confidence: 90%
“…(Rainey, 1967) and Aphis craccivora Koch (Johnson, 19571, and yet others can probably be taken as migrants, bearing in mind the long flights undertaken by their near relatives ; Empoasca fabae (Harris) is an example from the USA (Huff, 1963). Johnson (1969) gives many examples from around the world, and his list is stilf being added to, with examples from Japan (Asahina, 1970 ;Kisimoto, 1976 ;Oku & Kobayashi, 1974), Australasia (Fox 1973 ;Gutierrez et al, 1974 ;Helm, 1975 ;Hughes & Nicholas, 1974) and Canada (Rose et al, 1975 ;Rose, 1976) amongst other places. This impressive and growing list does make a strong case for assessing the evidence for, and the consequences of, long-range flight by every species of winged insect pest.…”
Section: Insect Migrations and The Need For Warningsmentioning
confidence: 99%
“…There has been little dispersal from the Norfolk County site; by 1971 L. luteator was still within 3.4 km of the release point (Griffiths 1973), and Rose's (1976) survey from 1972 to 1975 indicated no further movement. Dispersal from the Chatsworth site, in contrast, was rapid and extensive and Rose (1976) found L. luteator 100 km to the north and 305 km to the east by 1975. It is possible, however, that part of the movement indicated by his survey, at least the northward component of it, was due to our deliberate but hitherto unreported release of L. luteator in 1970 to a site near Hepworth, Grey County, 30 km northwest of the Chatsworth release point.…”
Section: Introductionmentioning
confidence: 99%
“…It became established on this sawfly in North America by one release in 1962 near Chatsworth in Grey County, Ontario, and by another in 1964 in Norfolk County, Ontario, with stock from Russia (Leningrad) and Austria, respectively (Griffiths and Lyons 1968). There has been little dispersal from the Norfolk County site; by 1971 L. luteator was still within 3.4 km of the release point (Griffiths 1973), and Rose's (1976) survey from 1972 to 1975 indicated no further movement. Dispersal from the Chatsworth site, in contrast, was rapid and extensive and Rose (1976) found L. luteator 100 km to the north and 305 km to the east by 1975.…”
Section: Introductionmentioning
confidence: 99%